Developing Social Science-History’s Comics- Based Learning Media for the Fifth Grade of Primary School In Pekanbaru City - Musnar Indra Daulay (International Journal of Research in Counseling and Education, 2017)
The purpose of this study was, therefore, to describe the processes and the results of developing the comic-based learning media on the subjects of Social Science-History for the fifth grade of primary school in Pekanbaru City. Research and Development (R&D) and Instructional Systems Design (ISD) of ADDIE was used to develop the media. Validity, practicality, and effectiveness tests were used to qualify the developed product. The developed comic-based learning media was stated “valid” by two media experts (63.33% and 90.83% respectively); by two material experts (77.92% and 96.67% respectively); whilst media validation was 83.33% and materials’ validation was 93.75%. The results of One-to One, Small Group and Field Trials were 88,54%, 93,23%, and 92,20% respectively. In conclusion, the research findings indicated that the developed comic-based learning media were stated valid and can be used in the intended context for the Fifth Grade of Primary Schools in Pekanbaru City.